2019
DOI: 10.11591/ijphs.v8i2.19022
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of post prandial glucose level in diabetic elderly

Abstract: Post prandial glucose (PPG) level describes the speed of glucose absorption after 2 hours of macronutrient consumption. By knowing this, we could get the big picture of insulin regulation function and macronutrient metabolism in our body. In elderly, age-related slower glucose metabolism leads to diabetes mellitus (DM) in older age. This study aimed to analyze the predictors of PPG level in diabetics elderly which consist of functional status, self-care activity, sleep quality, and stress level. Cross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
0
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
2
0
0
2
Order By: Relevance
“…Gender was not statistically related to blood sugar but in this study, it was found that most of the respondents were female, as well as the respondents that had high blood sugar and elderly were also found in females. This was in line with Sari and Manungkalit (2019) that the characteristics of the respondents were mostly women with advanced age and Post Prandial blood sugar level ³ 200 mg / dl (Hyperglycemia).…”
Section: Blood Sugar Content Based On Muna Tribe Community's Charactesupporting
confidence: 87%
See 1 more Smart Citation
“…Gender was not statistically related to blood sugar but in this study, it was found that most of the respondents were female, as well as the respondents that had high blood sugar and elderly were also found in females. This was in line with Sari and Manungkalit (2019) that the characteristics of the respondents were mostly women with advanced age and Post Prandial blood sugar level ³ 200 mg / dl (Hyperglycemia).…”
Section: Blood Sugar Content Based On Muna Tribe Community's Charactesupporting
confidence: 87%
“…It was found that more than half of the population had a low level of education. The low level of education in the Muna community was also in line with the demographic characteristics of the research results of the Elderly Diabetes in PKM Mulyorejo who found that most of the respondents were actually educated in junior high school (Sari & Manungkalit, 2019). Most of the respondents were also workers, but this was not related to blood sugar.…”
Section: Blood Sugar Content Based On Muna Tribe Community's Charactesupporting
confidence: 69%
“…Modifikasi gaya hidup penting sebagai titik awal bagi semua pasien DM, termasuk lanjut usia. Meskipun diet yang sangat ketat tidak direkomendasikan untuk orang lanjut usia, konseling untuk menghindari karbohidrat dalam jumlah besar pada satu kali makan dapat mengurangi lonjakan glukosa pada lansia (Purnama Sari & Manungkalit, 2019). Kegiatan penyuluhan mengenai pengendalian kadar glukosa sangat diperlukan oleh peserta kegiatan sehingga pemahaman peserta meningkat.…”
Section: Jenis Kelaminunclassified
“…Post prandial glucose dapat dipengaruhi oleh faktor internal dan eksternal. Faktor internal meliputi glukosa, insulin, dan kortisol, sedangkan faktor eksternal terdiri dari aktivitas fisik dan makanan yang dikonsumsi (Sari & Manungkalit, 2019). Respons glikemik dipengaruhi oleh banyak faktor sepeti jenis karbohidrat, jumlah karbohidrat yang dikonsumsi, makronutrien lain (protein, serat, dan lemak), fungsi fisiologis organ (pankreas, lambung, tingkat penyerapan nutrisi di usus, dan pengosongan lambung), dan kecepatan makan.…”
Section: Pembahasanunclassified